Research and Development of Early Faults Diagnosis of Planetary Gear Trains - Fan Zhifeng; Zhang Rong; Wang Ting; Zhang Wei (Jixie chuandong)
The planetary gear train is an important rotating mechanical component, and its early faults diagnosis is an important means to avoid major accidents. Early faults diagnosis of planetary gear trains is bound to become the focus of scholars. The characteristics of early faults signals of planetary gear trains are analyzed, the research status of the early faults mechanism, signal acquisition methods, faults feature extraction and identification of planetary gear trains are combed, and the main problems in early faults diagnosis are summarized. Some suggestions are put forward, such as the research of early compound faults mechanism based on the dynamic model, the research of early faults signal acquisition method based on the multi-sensor, the research of early faults characteristic index based on multi-domain analysis, the research of early faults diagnosis based on numerical model and so on. It can be used as a reference for further research on early faults diagnosis of planetary gear trains.